Association between law enforcement seizures of illicit drugs and drug overdose deaths involving cocaine and methamphetamine, Ohio, 2014–2019. (1st March 2022) - Zibbell, Jon E.; Clarke, Sarah Duhart; Kral, Alex H.; Richardson, Nicholas J.; Cauchon, Dennis; Aldridge, Arnie
Abstract: Background: The United States continues to experience a crisis of mounting opioid overdose deaths involving cocaine and methamphetamine (hereafter illicit stimulants). Law enforcement drug seizure data present a unique opportunity to examine the association between illicit-stimulant-involved overdose deaths (ISODs) and the illicit drug supply. Our objective is to better understand correlations between illicit drug market trends and increases in ISODs in Ohio in 2014–2019. Methods: This observational study analyzes the universe of ISODs and drug seizures in Ohio from 2014 to 2019. We use graphs and descriptive statistics to characterize trends over time and estimate a time series model of their association. ISODs were summed to yield monthly statewide counts of seizures containing methamphetamine, cocaine, illicitly manufactured fentanyl (IMF), and other non-IMF opioids (e.g., heroin). All rates were calculated per 100, 000 persons. Results: Roughly 80% of ISODs in Ohio from 2014 to 2019 involved an opioid, with IMF co-occurring in 90% of ISODs by 2019. Methamphetamine and cocaine seizures containing IMF were associated with 0.439 (p < .01) and 0.457 (p < .01) additional deaths per 100, 000 persons per month, respectively. IMF seizures not containing cocaine nor methamphetamine were also associated with additional ISODs (0.119, p < .01) and seizures of illicit stimulants not containing IMF were not associated with ISODs. Conclusions: The number of ISODs was extremely high when IMF was co-involved and relatively low without IMF involvement. By demonstrating how supply-side trends correspond with ISOD rates, the current study bolsters the analytical utility of law enforcement seizures and complements growing literature in the field. Highlights: Illicit stimulant OD risk is extremely high when IMF is involved and low when IMF is not. Cocaine and methamphetamine may serve as unwitting exposure to IMF. Study demonstrates utility of law enforcement drug exhibits for public health research. Racial variation in ISODs requires interventions tailored to race & residency of at-risk communities. Racial/geographic variation among ISODs demonstrate important nuances within illicit stimulant crisis.